Spirulina as a protein source in the nutritional recovery of Wistar rats - Moreira,Lidiane Muniz (2013)
This study was aimed at evaluating the effects of Spirulina (Arthrospira) as a protein source in the nutritional recovery of rats subjected to protein malnutrition. In order to understand such effects, responses of the developing body, serum biochemical profile, and blood count of animals were analyzed. A total of, 23 Wistar Rattus norvegicus were given a proteic diet (AIN-93G adapted) in malnutrition phase (phase I) for 10 days. After this period, the rats were separated into four groups according to the protein source (recovery phase): Control (C), casein 12%; Spirulina level I (S1), Spirulina 8.8% + casein 5.0%; Spirulina level II (S2), Spirulina 17.6% + casein 0.15%, and Spirulina level III (S3), Spirulina 26.4%. Recovery phase (phase II) lasted 30 days. In both the phases, the consumption and body weight of the rats were monitored daily and weekly, respectively. The S1 treatment showed the highest values of Feed Efficiency Ratio (FER) and Quotient of Protein Efficiency Ratio (QPE) (p<0.05). Significant differences among the treatments were found mainly in the levels of serum lipids, and S2 diet caused an increase in such responses (p<0.05). These results demonstrated that the nutritional recovery of animals was enabled by different concentrations of Spirulina.